Economic model of forestry adaptive capacity in the context of climate change - Bezrukova Tatiana; Gyiazov Aydarbek; Kuksova Irina (BIO Web of Conferences)
The article presents the theoretical foundations for the application of the economic model and the adaptive potential of forestry in the context of climate change, since the conservation and rational management of all types of forests is recognized as a critical factor in economic and social development and environmental protection. It is assumed that the model will be constructed as a weighted directed graph, which describes various methods for calculating the weight coefficients of the model based on statistical assessment and expert assessment, and also provides recommendations for their application to assess relationships of various natures. The developed economic model of the adaptive potential of forestry in the context of climate change will optimize the structure of forests taking into account probable climate changes, preserving their forestry and biological values, and increasing resistance to insect pests and forest diseases. Secondary resources will be preserved, and ecosystem services will be increased, fire hazard and losses from the impact of negative climatic phenomena will be reduced. A distinctive feature of which is the low level of resource provision and management potential, the need to consolidate as the main direction of development the adaptive potential for substantiating technologically simplified stages, with the development of standard organizational tools for applied use.